Developing Song Reproduction Drill to Improve Solfeggio Learning Achievement - Jagar Lumbantoruan (ADI Publisher, 2020)
This article aims to describe of how to improve the learners ability and selfeggio learning achievement by developing the drills of song reproduction, at the music major, art and language faculty, Padang state university west sumatera Indonesia. Learners’ prior ability was low since they have never been taught about music before in their former schools, no learning experience about solfeggio, no experience about procedural solfeggio. The writer intended to conduct an experimental research on the basis of production research by designing a new model of solfeggio learning for the teachers and the learners as well, by following mixed research methodology.The design phase consisted of; designing learning activity and the procedures. Developmental phase consisted of; developing the lesson plan and all things dealing with learning solfeggio.The research result proved that the new designed model of learning is helpful, valid, reliable, and practical to use either by the teachers or by students.